A few remarks on the role of hypertexts in the glottodidactic process - Szerszeń, Paweł (Glottodidactica, 2010)
In the contemporary foreign language didactics hypertexts play an increasingly important role, which is reflected in the glottodidactic discourse. The aim of the article is a juxtaposition of the elements which facilitate or limit reception of hypertexts in the glottodidactic process. Accordingly, the main problems which appear during student’s work with hypertexts are listed, and solutions to some of them are also suggested. Moreover, the arguments presented are in favour of the application of hypertexts in the glottodidactic process.